Цитадель: [роман] / Арчибальд Кронин ; перевод с английского Марии Абкиной - Кронин Арчибальд Джозеф (Иностранная литература, 2019)
Экземпляры: Ф. 12 (20231123) / Инвентарный номер: 50162 / Цена: 220.00 / Авт.знак: К 83 / ББК: 84(4Вел)